Repeated-sprint training with blood flow restriction: A novel approach to improve repeated-sprint ability? - Mckee, J. R.; Girard, O.; Peiffer, J. J.; Scott, B. R (Strength and Conditioning Journal, 2023)
Team sport athletes commonly perform repeated short-duration sprints (=10 seconds) separated by brief recovery periods (=60 seconds). The ability to maintain performance over a series of sprints is termed repeated-sprint ability (RSA). The physiological limiters of RSA include decreased force production capacity, insufficient energy supply, and metabolite accumulation. These limiting factors can be improved through repeated-sprint training, with greater RSA gains when performing this training with systemic hypoxia (i.e., reduced fraction of inspired oxygen). Exercising with blood flow restriction (BFR) causes localized hypoxia and a substantial metabolite load, which may provide an adjunct training method to improve RSA. Training with BFR augments muscular strength and adenosine triphosphate supply, which may improve subsequent sprint performance. Improved aerobic fitness, phosphocreatine resynthesis, and metabolite removal from BFR training could also enhance between-sprint recovery to resist fatigue. Despite the possible physiological benefits of repeated-sprint BFR training to improve RSA, there are no published reviews to collate this information. Therefore, this review proposes a theoretical framework for how BFR training could combat fatiguing factors and improve RSA based on current knowledge of the physiological impact of repeated-sprint training and BFR. Finally, guidance will be provided regarding how practitioners may implement BFR training to improve RSA.